Parents’ Perceptions of Native and Local English Teachers for Young Learners in A Private English Institution in Jabotabek Areas in Indonesia - Agus Haris Munandar; Maya Puspitasari; Milawati Milawati (Journal of Social Research, 2026)
This study investigates parents’ perceptions of Native English Teachers (NETs) and Local English Teachers (LETs) who teach young learners aged 3 to 12 at a private English language institution across the Jabotabek region of Indonesia. Using an explanatory sequential mixed-methods design, the study analyzed secondary survey data from 504 parents and conducted semi-structured interviews with 11 purposively selected participants. The quantitative findings revealed that 83.9% of respondents considered NETs important for their children's English education, with increased learner motivation (62.2%) and improved speaking proficiency (56.5%) identified as the primary reasons. Qualitative findings indicated that parents associated NETs with stronger linguistic competence while recognizing LETs for their pedagogical strengths, including effective instructional scaffolding, cultural understanding, and age-appropriate classroom management. The study identified personal experience, institutional marketing practices, and the ideology of native-speakerism as key sociocultural factors shaping parental preferences. A notable contradiction emerged regarding first-language use: although parents valued LETs' ability to use Bahasa Indonesia to clarify difficult concepts, they also perceived this practice as reducing learners' exposure to English. Overall, the findings suggest that parental preferences reflect a complex interaction among linguistic bias, perceived motivational value, and sociocultural influences, with native-speakerism remaining a dominant, yet nuanced, factor in Indonesia's private English as a Foreign Language (EFL) sector.